MARJINALISASI WANITA PADA RUBRIK KONSULTASI KARIER DALAM MAJALAH KARTINI: TINJUAN ANALISIS WACANA KRITIS - Hi Muhammad, Hujaefa; Sumarlam, Sumarlam (Yayasan Akrab Pekanbaru, 2018)
Women work is an achievement in itself. However, there are times when working women contribute to social problems. The media participates in this practice. This study aims to (1) analyze the text to see how women are marginalized through language constructs, (2) to analyze media behavior toward career women's marginalization, and (3) to analyze how social behavior in society contributes to the marginalization of career women. This research takes the data source in Kartini magazine on career consultation rubric. This research uses the analysis of critical discourse of van Dijk. The results show that in text analysis (macro structure, superstructure, and microstructure), social cognition analysis, and social analysis together form a marginalization in career women. Keywords: discourse analysis, van Dijk, Kartini magazine, Rubric Career Consultation